2011
DOI: 10.1063/1.3626598
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of the electric field effect on magnetization and magnetic anisotropy of FeCo/MgO(001) thin film

Abstract: The magnetization and magnetic anisotropy of FeCo/MgO(001) thin film under electric field were investigated by the first-principles calculations. Three different interface configurations were considered: Co/Fe/MgO, Fe/Co/MgO, and FeCo/FeCo/MgO. It was found that the perpendicular anisotropy was preferred for all the configurations and enhanced with increasing electric field, which was consistent with experimental results. Furthermore, our calculations indicated that the FeCo/FeCo/MgO was the most stable config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 34 publications
6
37
0
Order By: Relevance
“…Much research has been carried out to understand and improve the properties of this voltage effect [3][4][5][6][7][8][9][10]. The mechanism can be understood as a charge accumulation/subtraction or shift of band filling at the metal/dielectric interface as a result of the application of voltage [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been carried out to understand and improve the properties of this voltage effect [3][4][5][6][7][8][9][10]. The mechanism can be understood as a charge accumulation/subtraction or shift of band filling at the metal/dielectric interface as a result of the application of voltage [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…(4), the PMA of the FL also depends on the EF dependent DM s However, He et al 26 has reported that the change in Ms under EF, i.e., DMs is less than 3% at E ÂŒ 1 V/nm in a CoFe-MgO system. Thus, the value of DMs can be neglected, and Eq.…”
mentioning
confidence: 96%
“…Since the magnetocrystalline anisotropy determines the preferential orientation of magnetization, it may yield entirely new devices for magnetic data storage if the magnetocrystalline anisotropy can be tuned by electric fields. Recently, manipulation of magnetocrystalline anisotropy by applying an electric field has been studied and achieved in many systems with ferromagnetic metallic interfaces (surfaces) 18,[30][31][32][33][34][35][36] as well as at the interfaces (surfaces) of dilute magnetic semiconductors. 37,38 In particular, Maruyama et al 35 obtained a significant change in perpendicular magnetocrystalline anisotropy at the Fe/MgO (001) interface by an electrical voltage, which reached up to 40% in energy difference for a relatively small applied fields in the order of 100 mV/nm, as shown in Fig.…”
Section: Tuning Of Magnetocrystalline Anisotropymentioning
confidence: 99%